2017
DOI: 10.1111/peps.12251
|View full text |Cite
|
Sign up to set email alerts
|

The experience of being envied at work: How being envied shapes employee feelings and motivation

Abstract: We develop and test a theoretical framework delineating the dual affective and motivational experiences arising from perceptions of being envied in the workplace. We theorize that being envied can be pleasantly or unpleasantly experienced with opposite downstream effects on motivation and job performance. We test our model in two field studies using a sample of government employees (Study 1) and a sample of employees in the financial industry (Study 2). Our results indicate that being envied can elicit unpleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 90 publications
4
74
0
Order By: Relevance
“…We found that pride mediated the effect of achievements on motivation. The link between pride and motivation has been demonstrated in related domains ( Williams and DeSteno, 2008 ; Hofmann and Fisher, 2012 ; Lee et al, 2017 ), but the full mediation from system-generated social media posts on personal achievements via pride on motivation has not been shown before. Since pride was significantly higher in the own achievement group than in the other two conditions, we interpret it as pride stemming from one’s own achievement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that pride mediated the effect of achievements on motivation. The link between pride and motivation has been demonstrated in related domains ( Williams and DeSteno, 2008 ; Hofmann and Fisher, 2012 ; Lee et al, 2017 ), but the full mediation from system-generated social media posts on personal achievements via pride on motivation has not been shown before. Since pride was significantly higher in the own achievement group than in the other two conditions, we interpret it as pride stemming from one’s own achievement.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, no studies have tested the mediating role of pride on motivation, although some authors speculated that positive affect might be a mediator ( Delin and Baumeister, 1994 ). There are, however, studies showing that pride can increase perseverance ( Williams and DeSteno, 2008 ), goal importance ( Hofmann and Fisher, 2012 ) and work engagement ( Lee et al, 2017 ). It might thus be that personal achievements lead to higher motivation via a mediating role of pride.…”
Section: Introductionmentioning
confidence: 99%
“…Although envied employees may experience two completely opposite emotions, when being envied causes unpleasantness, it will cover up and gradually replace shortterm positive emotions, and affect employees' work engagement in a negative way [3]. On the one hand, when employees perceive themselves as the target of another person's envy, they not only experience tension and anxiety, but also have to consider coping strategies, which will consume a lot of time and energy.…”
Section: A Being Envied and Work Engagementmentioning
confidence: 99%
“…Considering that one's energy is limited, when employees are invested too much in workplace envy, the vitality and vigor in work will be reduced accordingly. On the other hand, some employees may take the initiative to reduce work engagement in order to avoid being the "target" of others' attacks [3]. In addition, Ma, Huang and Zhu (2014) also found that interpersonal relationship pressure will negatively affect the performance of employees.…”
Section: A Being Envied and Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation